European collections of scientific instruments, 1550-1750 - Strano, Giorgio (History of science and medicine library ;, 2009)
These selected studies on sixteenth and eighteenth centuries European collections of scientific instruments, which were part of the princely 'wunderkammern', delineate an up-to-date-panorama about the formation of the most important museums of the history of science.